2022
DOI: 10.3390/joitmc8030122
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Digital Marketing Tools to Develop the Innovative SFSC Players’ Business Models

Abstract: The traditional global food supply chains are not just complex, but they do not support the sustainability of agriculture. The business models with the greatest growth potential are those that would allow consumers to buy more directly from producers. Before COVID-19, these alternatives were not just popular but had a relatively high market share compared to post COVID-19 era. However, due to the pandemic and the changes in consumers’ purchasing behavior, the players of short food supply chains had to adapt to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
1
2
0
1
Order By: Relevance
“…Numerous research (Cheng et al, 2021;Csordás et al, 2022;Dahlberg et al, 2015;Dwivedi et al, 2021;ElMaraghy et al, 2021;Figueiredo et al, 2021;Hong et al, 2006) have revealed a positive association between ease of use and technology adoption, which supports its inclusion in our hypotheses and is consistent with TAM.…”
Section: H3supporting
confidence: 89%
“…Numerous research (Cheng et al, 2021;Csordás et al, 2022;Dahlberg et al, 2015;Dwivedi et al, 2021;ElMaraghy et al, 2021;Figueiredo et al, 2021;Hong et al, 2006) have revealed a positive association between ease of use and technology adoption, which supports its inclusion in our hypotheses and is consistent with TAM.…”
Section: H3supporting
confidence: 89%
“…Those agri-food organizations that embraced digital marketing during the pandemic experienced a threefold increase in sales volume. This reflects a shift in consumer behavior towards online purchases, without overlooking the importance of voice-to-voice interaction (Csordás et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Az üzletvitel szinte minden iparágban egyre szorosabban kötődik a digitális világhoz. A digitális környezethez való folyamatos alkalmazkodás nélkül nagyon nehezen maradhat életben bármely vállalkozás [5]. Ez a lemaradás jelentős versenyhátránnyal jár, hiszen az informatikai erőforrások, azok adaptációs képessége hozzájárul a teljesítményük és eredményességük növeléséhez.…”
Section: Bevezetésunclassified